Design and development a small stirling engine - Nurul Huda, Baso (2012)
A stirling engine is a heat engine operating by cyclic compression and expansion of air or other gas, the working fluid, at different temperature levels such as net conversion of heat energy to mechanical work. The Stirling engine was noted for its high efficiency compared to steam engines, quiet operation, and the ease with which it can use almost any heat source. The purpose of the project, are to design and fabricate the stirling engine. In this project, all the components were fabricating using milling machine, cutter, lathe machine, and CNC machine. Besides that, all the components will be assembled and the performance of stirling engine will be analyzed. Schmidt Analysis of Ideal Isothermal equation were use to find the performance of stirling engine in watt. The fin at cold cylinder will be analyzed using fins heat transfer equation.